PERKEMBANGAN DAN PERAN BANK SYARIAH DALAM MENYONGSONG MASA DEPAN KEUANGAN ISLAM DI INDONESIA - Umi Fikriyah; Muhammad Syahrul Arifin; Hasna Huwaidah; Lilis Arviani; Ade Gunawan; Muhammad Taufiq Abadi (CV. ALIM'SPUBLISHING, 2024)
The aim of this research is to explain the development and role of financial institutions that use sharia principles, one of which is sharia banks in welcoming the future of Islamic finance in Indonesia. This research method uses a qualitative method with a type of library research with two types of secondary data, namely published papers in the form of books, reputable scientific articles, journal reviews, and reports from official organizations. The results of this research conclude that Sharia Banks in Indonesia are one of the financial institutions that have the main task of providing credit and services in the field of payments and money circulation accompanied by sharia principles. The development of sharia banks in Indonesia has become a benchmark for the implementation of sharia economics and its existence in Indonesia. The slowdown in the growth of Islamic banks related to the economic symptoms that are occurring can be overcome by consolidation from internal parties. Islamic banks in Indonesia play an important role in the future of sharia finance. The existence of an increase in the quality of sharia banks in national sharia banking does not rule out the possibility of increasing the competitiveness of sharia banks at the global level. Sharia banks have achieved quite rapid achievements considering that the majority of Indonesian people are Muslim.